Student Evaluation of Teaching: Methodological Critique - Sproule, Robert (Education Policy Analysis Archives, 2000)
The purpose of the present work is twofold. The first is to outline two arguments that challenge those who would advocate a continuation of the exclusive use of raw SET data in the determination of "teaching effectiveness" in the "summative" function. The second purpose is to answer this question: "In the face of such challenges, why do university administrators continue to use these data exclusively in the determination of 'teaching effectiveness'?"